2019
DOI: 10.4178/epih.e2019010
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient intake patterns and breast cancer risk among Jordanian women: a case-control study

Abstract: OBJECTIVES: Breast cancer (BC) is the most common type of cancer worldwide. Globally, BC is rapidly becoming a major common health problem among women. This study aimed to evaluate the association between nutrient intake patterns and BC risk among Jordanian women.METHODS: A total of 400 Jordanian women 20-65 years of age were recruited in this case-control study. Two hundred women recently diagnosed with BC were matched in age, income, and marital status to 200 BC-free women. A food frequency questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The antitumour effect of vitamin D is a popular research topic. Epidemiological studies have compared the relationship between serum vitamin D levels and prognosis in patients with breast cancer 25 and rectal cancer 26 and have found that the higher the serum level of vitamin D is, the better is patient prognosis. The regulatory relationship between vitamin D and tumours has not yet been elucidated, and its mechanism has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The antitumour effect of vitamin D is a popular research topic. Epidemiological studies have compared the relationship between serum vitamin D levels and prognosis in patients with breast cancer 25 and rectal cancer 26 and have found that the higher the serum level of vitamin D is, the better is patient prognosis. The regulatory relationship between vitamin D and tumours has not yet been elucidated, and its mechanism has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…This diet is high in dietary ber, calcium, folate, carotenes and phenolic compounds [39]. The association of these nutrients with BC risk has been suggested in several studies [40][41][42][43]. Furthermore, this dietary pattern is high in dietary antioxidants such as proanthocyanidines, avonoids, stilbenes and alpha-tocopherols [44,39] which could reduce cancer risk [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows participants' socio-demographic, anthropometric measurements, health and lifestyle characteristics. 15 Average age for cases was 48.9±0.63 years and 47.5±0.59 years for control. BMI, education level, employment status, smoking and family history of BC, were all significantly different as BC cases compared to the controls.…”
Section: Resultsmentioning
confidence: 95%